2019
DOI: 10.3390/nano9071006
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Secondary Dispersion of Modified Nanoparticles by Hot-Stretching to Enhance Dielectric and Mechanical Properties of Polyarylene Ether Nitrile Composites

Abstract: Enhanced dielectric and mechanical properties of polyarylene ether nitrile (PEN) are obtained through secondary dispersion of polyaniline functionalized barium titanate (PANI-f-BT) by hot-stretching. PANI-f-BT nanoparticles with different PANI content are successfully prepared via in-situ aniline polymerization technology. The transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopic instrument (XPS) and Thermogravimetric analysis (TGA) results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The texture of all PEN films are homogeneous and dense. Notably, the PEN (HQ/BP) film has the highest degree of orientation, and obvious lines can be observed in the cross‐sectional photos, which shows that this kind of PEN film is subjected to the greatest force and shows great toughness during stretching 26 . In addition, no obvious spherulites were observed in the cross‐sections of the four kinds of PEN films, which proves to a certain extent that these four PENs are all amorphous polymers.…”
Section: Resultsmentioning
confidence: 85%
“…The texture of all PEN films are homogeneous and dense. Notably, the PEN (HQ/BP) film has the highest degree of orientation, and obvious lines can be observed in the cross‐sectional photos, which shows that this kind of PEN film is subjected to the greatest force and shows great toughness during stretching 26 . In addition, no obvious spherulites were observed in the cross‐sections of the four kinds of PEN films, which proves to a certain extent that these four PENs are all amorphous polymers.…”
Section: Resultsmentioning
confidence: 85%
“…As can be seen from the figure that the glass transition temperature (T g ) of the pure PEN was about 170.0 • C, and with the increase of the BT@ZnPc-GO content, the T g of the BT@ZnPc-GO/PEN nanocomposites present a slight increase. This is because the nanoparticles are regarded as the physical crosslink points in the PEN matrix, which limit the movement of molecular chains, resulting in improvement of the T g of the nanocomposites [27]. In addition, the PEN used herein has a certain degree of crystallization, which is due to the large number of rigid p-phenyl and m-benzene segments contained in this structure (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with the addition of a nucleating agent in the PEN matrix, the nucleating agent promotes crystallization while also reducing the optimal crystallization temperature. It has been reported that the crystallization behavior of the polymer will affect the dielectric properties of the polymer based composites [27]. Figure 11 shows the dielectric properties of BT@ZnPc-GO-1/PEN composite film as a function of heat-treatment temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although having many benefits, the final properties of the nanocomposite will not only depend on the constituting materials but also on the processing methods. Generally, there are different synthetic strategies to get such nanocomposites, including hot pressing [73] , spin coating [74] and melt stretching [75,76] (Scheme 1-b).…”
Section: Strategies Of the Design Of Core-shell Batio 3 @Polymer/fluorinated Polymer Nanocompositesmentioning
confidence: 99%